Objektifikasi dan Kegagalan Intersubjektivitas dalam Novel “Duri dan Kutuk” Karya Cicilia Oday: Kajian Feminis Psikoanalisis - Ensadetha Iktisah; Anas Ahmadi; Moh. Ahsan Shohifur Rizal (Indo Publishing, 2026)
This study focuses on the doer/done-to relational pattern as represented through the relationship between the characters Adam and Eva. It reveals that this relationship demonstrates a failure to achieve intersubjectivity and thirdness, as well as how Eva’s curse is interpreted as a form of resistance and, at the same time, an expression of the failure to recognize female subjectivity within a patriarchal system. The aim of this research is to uncover forms of female objectification and the dynamics of power relations that hinder the creation of mutual recognition between men and women in literary texts. The method used is qualitative research with a psychoanalytic feminist approach based on Jessica Benjamin and a hermeneutic analysis approach based on Hans-Georg Gadamer. The data source of this research is the novel Duri dan Kutuk by Cicilia Oday, while the research data consist of narrative excerpts, dialogues, and character portrayals related to gender relations. The results show that the relationship between Adam and Eva represents a doer/done-to dominance pattern that positions Eva as an object of male desire and gaze. This relationship fails to achieve intersubjectivity due to the absence of mutual recognition of Eva as an autonomous subject. This failure also prevents the formation of thirdness as an equal relational space. Eva’s curse can be interpreted as a form of resistance to patriarchal domination, as well as an expression of the failure to acknowledge women’s subjectivity within unequal gender relations.